Comparative Study for Discrete Wavelet Transform Between Single and Double Detection Approach to Fault Classification on Transmission Line - Praikanok Lertwanitrot; Atthapol Ngaopitakkul; Santipont Ananwattanaporn (My University, 2024)
This study presented a novelty method for a protection relay using a microcontroller. The method able to detect and classify faults in high voltage transmission lines based on the Discrete Wavelet transform (DWT). In addition, novelty of proposed method when compared to traditional methods was a signal analysis process applied Clark's Transformation and Double Detection Technique. A performance of proposed method was verified by created experimental model in our KMITL laboratory. All fault types (SL, LL, DLG and 3P) were observed. This result of this study found that not only applied DWT method can improved the accuracy of signal analysis, applied Clark's Transformation able to filter noise of signal, without loss of information. Meanwhile, Double Detection Technique able to re-confirm the accuracy of fault detection and classify. Therefore, it results in the performance of a protection relay increase which is beneficial to the electrical system. It can increase the accuracy and reliability of the system.
Keywords: Power Systems Fault Detection; Power Systems and Technologies; Smart Grid and Power Systems